X-men: gold (2017), volume 2 ebook Evil empires. - Guggenheim, Marc (X-Men: Gold (2017), 2017)
Collecting X-Men Gold (2017) #7-12. What does the Secret Empire event have in store for the X-Men? Find out what the new landscape of the Marvel Universe looks like for Kitty, Storm, Colossus, Nightcrawler, Rachel Grey and Old Man Logan. Will they be able to survive in a world dominated by Hydra?